Variations in Leaf Traits Modulate Plant Vegetative and Reproductive Phenological Sequencing Across Arid Mediterranean Shrublands - Navarro, Teresa; Hidalgo-Triana, Noelia (Frontiers in Plant Science, 2021)
Leaf structural and nutrient traits are important for understanding plant ecological strategies (e.g., drought avoidance). We studied the specific leaf area (SLA), leaf carbon content (LCC), leaf nitrogen content (LNC), leaf phosphorous content (LPC) and the Phenophase Sequence Index (PSI) in 126 Mediterranean perennial species from pre-desert (SMS) and semi-arid (SaMS) to subalpine (SAS), alpine cushion (AcS) and oro-Mediterranean (AjS) shrublands which represent eight functional groups (evergreen and deciduous trees, evergreen large and half shrubs, deciduous large and half shrubs, succulents and perennial herbs). We analysed variation and relationships between leaf traits and PSI among shrublands, functional groups and within species with drought avoidance mechanisms. The 20–60% of SLA variation could be ascribed to differences between functional groups and only the 38–48% to different shrublands increasing from the pre-desert to the alpine. Alpine species displaying low PSI and N:P and high SLA, LNC, LPC, LCC and C:N. Conversely, pre-desert and semi-arid showed high PSI and low SLA. SLA mediate in the vegetative and reproductive phenological plant sequencing: high SLA is often associated with the overlapping in growth and reproductive phenophases with a seasonal reduction of vegetative growth, while low SLA is associated with vegetative and reproductive sequencing and a seasonal extension of vegetative growth. Species with drought avoidance mechanisms (e.g. semi-deciduous species) contribute to increase the mean values of the SLA and LNC because these species shows similar leaf and phenological patterns as the deciduous (high SLA and LNC and low PSI). The N:P indicate that only the alpine shrublands could present P limitations. The positive correlations between SLA and LPC and LNC and LPC (leaf economic spectrum) and the negative correlation between SLA and C:N were consistently maintained in the studied arid Mediterranean shrublands.